Objective assessment of nasal patency - Giotakis, Aristeidis I.; Vent, Julia (Facial plastic surgery, 2017)
The aim to objectify nasal airflow and patency is ongoing - many methods have been suggested, often lacking clinical relevance or showing weak correlations with patients' symptoms. It is crucial to thoroughly consult our patients presenting with nasal obstruction - and to inform them about realistic possible surgical outcomes. Often, a perfect-looking internal nose with a straight septum and normal-appearing turbinates does not guarantee a happy, symptom-free “owner.” A review of the literature and the current technical market is presented here to facilitate the rhinosurgeon's decision to perform pre- and postoperative objective measurements of nasal airflow. Recommendations by the societies have been included.